Dianthus burdurensis (Caryophyllaceae), a new species from South-western Turkey - Hamzaoğlu, Ergin; Koç, Murat (Phytotaxa, 2015)
Dianthus burdurensis is here described as a new species from Burdur province (Turkey). Its distribution, habitat, and IUCN category are also given, as well as a macro- and micromorphological comparison with the related species D. masmenaeus Boiss.